KARAKTERISTIK PASIEN TB PARU YANG PATUH DAN TIDAK PATUH BEROBAT DI PUSKESMAS PERUMNAS II KECAMATAN PONTIANAK BARAT PERIOD 1 JANUARI - 31 DESEMBER 2010 - ., Heldiastri K. Randung (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Background: Pulmonary tuberculosis (TB) is a global infectious disease thatwas causing mortality in the world. Indonesia ranks fifth in the world that hasthe largest number of pulmonary TB cases. Pulmonary TB treatment needs along time to achieve healing and needs a combination of several kinds ofdrugs. The adherence is absolutely needed in pulmonary TB treatment toreach out the goal. It is important to know the characteristics of pulmonary TBpatients who adherent and non-adherent in pulmonary TB treatment.Methods: The study was a descriptive study with cross-sectional design.Object: To investigate the characteristics of pulmonary TB patients whoadherent to treatment and non-adherent to treatment in Perumnas II primaryhealth center, West Pontianak, on January 01 to December 31, 2010.Results: The patients who adherent to pulmonary TB treatment are 86.48%that have characteristics: in range of age 20-29 years, male, grade ofeducation in senior high school, have good knowledge about pulmonary TBdisease, and did not have drug side effects. The patients who non-adherentto pulmonary TB treatment are 13.51% that have characteristics: in range ofage 20-49 years, female, grade of education in elementary school, have poorknowledge about pulmonary TB disease, and have drug side effects.Key words: Characteristics, Adherence, Treatment, TuberculosisNotes:*Medical School, Faculty of Medical, Universitas Tanjungpura, Pontianak,West Kalimantan; **Departemen of Pulmonology, General Hospital of dr.Soedarso, Pontianak, West Kalimantan; ***Departemen of Biochemistry,Universitas Tanjungpura, Pontianak, West Kalimantan